2014
DOI: 10.1007/s00221-014-3985-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the nausea-to-emesis continuum in non-human animals: refocusing on gastrointestinal vagal signaling

Abstract: Nausea and vomiting are ubiquitous as drug side effects and symptoms of disease; however, the systems that determine these responses are arguably designed for protection against food poisoning occurring at the level of the gastrointestinal (GI) tract. This basic biological pathway using GI vagal afferent communication to the brain is not well understood. Part of this lack of insight appears to be related to current experimental approaches, such as the use of experimental drugs, including systemic chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 89 publications
(101 reference statements)
2
14
0
Order By: Relevance
“…Emetogenic stimuli also induce gastric dysmotility. This has been used as an indirect marker of nausea in rodents but occurs likewise in non‐rodent species . Similar to previous reports, our study demonstrated that cisplatin at 6 mg kg −1 reduced gastric emptying and produced gastric distension, mainly due to the distension of the forestomach.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Emetogenic stimuli also induce gastric dysmotility. This has been used as an indirect marker of nausea in rodents but occurs likewise in non‐rodent species . Similar to previous reports, our study demonstrated that cisplatin at 6 mg kg −1 reduced gastric emptying and produced gastric distension, mainly due to the distension of the forestomach.…”
Section: Discussionsupporting
confidence: 91%
“…This has been used as an indirect marker of nausea in rodents 20,21,43 but occurs likewise in non-rodent species. 44,45 Similar to previous reports, 15,20,21,46 our study demonstrated that cisplatin at 6 mg kg −1 reduced gastric emptying and produced gastric distension, mainly due to the distension of the forestomach. Gastric dysmotility associated with this high dose of cisplatin was observed as soon as 20 minutes after administration 21 and lasted for at least 3 days.…”
Section: Discussionsupporting
confidence: 90%
“…In what are now largely separate silos of research, the importance of vagal function has been implicated in studies of: microbiome influences on symptom experience [44]; appetite [45]; nausea and vomiting [46]; fatigue [47]; drowsiness and sleep problems [48]; and peripheral pain sensation [49]. It is also important to note that nausea does not require a precipitating impact on the gut; nausea can be provoked by effects in the central nervous system components of the gut-brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals often experience nausea without vomiting (Horn, 2014; Lackner, 2014). Moreover, individuals describe nausea in various ways (Graybiel et al, 1968; Muth et al, 1996), in accordance with the wide range of perceptions that can occur prior to vomiting.…”
Section: Introductionmentioning
confidence: 99%